2022
DOI: 10.3390/fractalfract6070386
|View full text |Cite
|
Sign up to set email alerts
|

Second Derivative Block Hybrid Methods for the Numerical Integration of Differential Systems

Abstract: The second derivative block hybrid method for the continuous integration of differential systems within the interval of integration was derived. The second derivative block hybrid method maintained the stability properties of the Runge–Kutta methods suitable for solving stiff differential systems. The lack of such stability properties makes the continuous solution not reliable, especially in solving large stiff differential systems. We derive these methods by using one intermediate off-grid point in between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, this resulted in a higher condition number than both y n+ 7 4 and y n+ 5 2 . On a final note, the results of both methods presented in this study outperform the second-order and fourteenth-order second derivative method of [35] with less function evaluations and computational time.…”
Section: Examplementioning
confidence: 71%
See 4 more Smart Citations
“…However, this resulted in a higher condition number than both y n+ 7 4 and y n+ 5 2 . On a final note, the results of both methods presented in this study outperform the second-order and fourteenth-order second derivative method of [35] with less function evaluations and computational time.…”
Section: Examplementioning
confidence: 71%
“…Table 3 showed that the block hybrid method y n+ 5 2 performed better than y n+ 7 4 using the same initial conditions, especially for x = 50. Nevertheless, both methods, though of order five, outperformed Yakubu et al's [35] fourteenth-order method, as summarized in Table 4. Figure 3, which is a log-log plot of the errors and step sizes, showed that, while both methods performed at par for y 1 (x), the same was not the case for y 2 (x) because y n+ 7 4 performed better than y n+ 5 2 .…”
Section: Numerical Experimentsmentioning
confidence: 86%
See 3 more Smart Citations